Pengaruh Intellectual Capital, Profitabilitas, dan Harga Saham Terhadap Nilai Perusahaan Transportasi dan Logistik yang Terdaftar di BEI Tahun 2020-2022 - Jannah, Miftaqul; Ardiana, Meta (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
This study intends to insvestige the impact on Intellectual Capital Profitability, and Stock Price about the benefit of the firm in the transportation and logistics sector. It employs a quantitative utilize secondary data sources. The study focuses regarding campanies traded the Indonesia Stock Exchange (IDX) starting 2020 up to 2022. Gathering information uses this targeted sampling technique, yielding 48 data points. Secondary data is sourced from company annual reports, and data analisys is conducted using SPSS 29 software. Results indicate Intellectual Capital contributes positively to company value in the transportation and logistics sector, Profitability positively influences firm value, and Stock Price also shows a beneficial impact on company value in this sector.